Transportation Security Framework for a Medium-Sized City - Fries, Ryan; Chowdhury, Mashrur; Dunning, Anne (European Journal of Transport and Infrastructure Research, 2008)
Terrorist attacks have made security preparedness unquestionably necessary in all cities. While major metropolitan areas have long recognized that their global visibility has required strong security operations, many medium-sized cities, specifically those of the U.S. and European Union, now face the need to establish transportation security frameworks for the first time. This paper assesses the resources available to help medium-sized cities begin the task of creating such systems. This assessment presents infrastructure risk assessment tools, identifies infrastructure and funding resources, and creates a process for developing a security framework to connect agencies responsible for transportation security in these metropolitan areas. Descriptions of transportation security framework practices at the national level had led to the preparation of a transportation security framework for Greenville, South Carolina, USA, to serve as a prototype that other medium-sized cities can emulate. This security framework can serve as either a checklist to ensure security coverage in existing asset management systems and intelligent transportation systems architectures such as those frequently used in the U.S., Europe, and Japan, or it can provide baseline structure for developing a new transportation security framework for cities in developing countries.